2017
DOI: 10.1016/j.jor.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dynamics in 3D glenohumeral position between primary dislocated shoulders and contralateral healthy shoulders

Abstract: A B S T R A C TBackgrounds: After shoulder dislocation, kinematic changes in shoulder, including translation of the humeral head, ensue. There have been many attempts to measure these changes using motion measurement techniques, but in vivo three-dimensional (3D) glenohumeral changes have not been appreciated until now. The purpose of this study was to measure and analyze changes in glenohumeral translation in patients with shoulder dislocation and compare these changes with healthy shoulder. Methods: We inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“… MRI Kiss (1997) 28 case-control ☆☆ ☆☆ 4/9 stars Reproducibility from 2 measurements (2 SD): 0.76 mm for internal rotation, 0.28 mm for external rotation, 1.52 mm for overhead position. von Eisenhart-Rothe (2002) 9 case-control ☆☆☆ ☆☆ † ☆☆☆ 8/9 stars N/A CT Kim (2017) 27 case-control ☆☆☆ ☆☆ † ☆☆ 7/9 stars Estimated root-mean-square errors (RMSE): 0.43 mm for the in-plane direction, 1.53 mm for the out-of-plane direction. Matsumura (2019) 35 case-control ☆☆☆ ☆☆ † ☆☆☆ 8/9 stars Reportedly not validated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… MRI Kiss (1997) 28 case-control ☆☆ ☆☆ 4/9 stars Reproducibility from 2 measurements (2 SD): 0.76 mm for internal rotation, 0.28 mm for external rotation, 1.52 mm for overhead position. von Eisenhart-Rothe (2002) 9 case-control ☆☆☆ ☆☆ † ☆☆☆ 8/9 stars N/A CT Kim (2017) 27 case-control ☆☆☆ ☆☆ † ☆☆ 7/9 stars Estimated root-mean-square errors (RMSE): 0.43 mm for the in-plane direction, 1.53 mm for the out-of-plane direction. Matsumura (2019) 35 case-control ☆☆☆ ☆☆ † ☆☆☆ 8/9 stars Reportedly not validated.…”
Section: Resultsmentioning
confidence: 99%
“… 3 , 39 Recurrent as well as first-time events can give rise to chronic shoulder instability and diminished shoulder and upper limb function. 2 , 7 , 8 , 9 , 23 , 27 , 31 , 43 Ultimately, shoulder instability can reduce quality of life. 18 , 36 …”
mentioning
confidence: 99%
“…4,13 A previous study using 3-and 2-dimensional model image registration techniques showed that the center of the humeral head was located 2.3 mm more anteriorly in cases of traumatic anterior shoulder instability at 20 of shoulder abduction with neutral rotation than in the contralateral side. 9 Another study using magnetic resonance imaging showed that the center of the humeral head was located 1.5 mm more anteriorly in traumatic anterior shoulder instability, at 90 of shoulder abduction with neutral rotation, than on the contralateral side. 26 In addition, various studies have investigated the humeral head position several months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the center of the humeral head is located anteriorly in anterior shoulder instability 9 , 26 and that the pathological position of the humeral head could be a cause of discomfort, anxiety, and/or a painful shoulder. 4 , 13 A previous study using 3- and 2-dimensional model image registration techniques showed that the center of the humeral head was located 2.3 mm more anteriorly in cases of traumatic anterior shoulder instability at 20° of shoulder abduction with neutral rotation than in the contralateral side.…”
Section: Discussionmentioning
confidence: 99%
“…Ethical considerations, in line with previous studies, led to recruitment of eight volunteers to participate in the invasive validation experiment [ [23] , [24] , [25] ]. The guidelines published by Koo et al, in 2016 were used to indicate the level of reliability [ 16 ].…”
Section: Methodsmentioning
confidence: 97%